2003
DOI: 10.1093/chemse/bjg067
|View full text |Cite
|
Sign up to set email alerts
|

No Influence of Scopolamine Hydrobromide on Odor Detection Performance of Rats

Abstract: Despite speculation that the muscarinic cholinergic antagonist, scopolamine, may influence the olfactory sensitivity of rats, there have been no definitive studies on this point to date. In this study, we examined the influence of a range of doses of scopolamine hydrobromine (namely, 0.10, 0.125, 0.15 and 0.20 mg/kg i.p.) on the odor detection performance of 15 adult male Long-Evans rats to ethyl acetate. Air-dilution olfactometry and a go/no-go operant signal detection task were employed. The drug conditions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
14
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…In our research, odor-detection performance was not affected by infusions of scopolamine, as shown in the olfactory perception test. Such data agree with a recent study reporting that systemic administration of different doses of scopolamine, which are known to influence odor memory and learning, did not cause alterations in the odor-detection performance of rats (Doty et al 2003). Secondly, the duration of the scopolamine action in the brain is an aspect to consider in the explanation of our findings.…”
Section: Discussionsupporting
confidence: 93%
“…In our research, odor-detection performance was not affected by infusions of scopolamine, as shown in the olfactory perception test. Such data agree with a recent study reporting that systemic administration of different doses of scopolamine, which are known to influence odor memory and learning, did not cause alterations in the odor-detection performance of rats (Doty et al 2003). Secondly, the duration of the scopolamine action in the brain is an aspect to consider in the explanation of our findings.…”
Section: Discussionsupporting
confidence: 93%
“…For example, the blockade of mAChRs may attenuate olfactory sensitivity, alter sensitivity to the foot shock, and/or alter the odor-shock associative plasticity. Our odor investigation experiment along with another report (Doty et al 2003) suggests that scopolamine does not significantly affect olfactory processing, at least with the odorant concentrations used here. A prior study has also demonstrated that systemic scopolamine does not affect foot-shock sensitivity in mice (Anagnostaras et al 1999).…”
supporting
confidence: 64%
“…To assess olfactory capabilities, Csf1 op/op and WT littermates were subjected to classic buried food challenges [73], [74], [75]. On the first evening of the tests, each mouse was placed in an arena (86 cm×63 cm×18 cm) for a habituation period.…”
Section: Methodsmentioning
confidence: 99%